2008
DOI: 10.1152/ajplung.00048.2007
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter exposure induces persistent lung inflammation and endothelial dysfunction

Abstract: Epidemiologic and animal studies have shown that exposure to particulate matter air pollution (PM) is a risk factor for the development of atherosclerosis. Whether PM-induced lung and systemic inflammation is involved in this process is not clear. We hypothesized that PM exposure causes lung and systemic inflammation, which in turn leads to vascular endothelial dysfunction, a key step in the initiation and progression of atherosclerosis. New Zealand White rabbits were exposed for 5 days (acute, total dose 8 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
122
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 31 publications
13
122
0
2
Order By: Relevance
“…This finding is suggestive of a bone marrow response, causing an increase in red blood cells. A consistent link between inhalation of pollutants and the bone marrow response has previously been reported, indicating a strong link between lung and systemic events (37). The elevation in erythrocytes and hematocrit observed in the present study corroborate previous findings that showed a rise of erythrocytes and hematocrit in young male smokers (18).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is suggestive of a bone marrow response, causing an increase in red blood cells. A consistent link between inhalation of pollutants and the bone marrow response has previously been reported, indicating a strong link between lung and systemic events (37). The elevation in erythrocytes and hematocrit observed in the present study corroborate previous findings that showed a rise of erythrocytes and hematocrit in young male smokers (18).…”
Section: Discussionsupporting
confidence: 93%
“…We conclude that lovastatin downregulates the PM10-induced overactive bone marrow by attenuating PM10-induced systemic inflammatory responses. polymorphonuclear leukocytes; interleukin-6 MANY WELL-DOCUMENTED STUDIES have supported the concept that ambient particulate matter (particles less than 10 m or PM 10 ) exposure induces systemic inflammatory responses, characterized by an increase in circulating proinflammatory mediators (10,22) and blood elements such as leukocytes (8, 16) or platelets (18). These systemic responses to PM 10 exposure have been implicated in the risk for downstream cardiovascular events (4).…”
mentioning
confidence: 94%
“…The present study was designed to determine the effects of statins on the bone marrow of rabbits exposed to PM 10 (EHC-93). We used a well-established rabbit model of PM 10 exposure for 3 wk (6,16,22) and determined the bone marrow response by using thymidine analog, 5=-bromo-2=-deoxyuridine (BrdU) to label the dividing myeloid cells in the bone marrow. BrdU labeling enables morphological differentiation to quantify newly released PMNs from the bone marrow.…”
mentioning
confidence: 99%
“…PM 2.5 can reach deep in the lung to the small airway and alveoli, 6 and directly cause lung inflammation and injury. [7][8][9][10][11][12][13] The pulmonary complications may lead to detrimental effects on other organs, particularly cardiovascular dysfunction such as systemic microvascular dysfunction and thrombosis. 1,2,4,5,13 A recent study demonstrated that short-term UPM exposure triggered the activation of primary hemostasis in healthy mice, with no substantial secondary hemostasis activation, leading to arterial but not venous thrombosis.…”
Section: Introductionmentioning
confidence: 99%